Retail employees’ performance expectations and perceptions: gaps between employees’ and supervisors’ evaluations - Tay, A.; Dar, O.L. (2011)
This study examines the extent to which perceptual gaps exist between retail employees’ self-reported performance quality and productivity expectations and their perceptions. It also compares employees’ expectations and their immediate supervisors’ perceptions of employee performance. We adopted the expectation disconfirmation theory from the services marketing and consumer behaviour studies to extend human resource management literature on the perceptions of employee performance. Results from a dyad study of 292 employees and 106 supervisors from a large international retailer in Malaysia revealed that there were negative mean score gaps between employees’ self-reported performance perceptions (P) and their expectations (E). Comparatively, the employees had expected to perform better than they, or even their immediate supervisors perceived they had achieved. While the mean scores for employees’ and their supervisors’ perceptions of employees’ performances were almost similar, there were gaps between both of their perceptions and employees’ self-reported performance expectations. This preliminary research empirically highlights the E - P performance gaps of retail employees. Retailers would benefit if they could proactively identify and thereby take constructive and practical measures to narrow the perceptual gaps and drive employees to deliver better service quality.